THU0539 Clinical Presentation of Cryopyrin-Associated Periodic Syndrome (CAPS) in Carriers of the Q703K Mutation in the CIAS1/NLRP3 Gene: Genotype-Phenotype Characterization of a Family. (9th June 2015) - Germano, G.; Soriano, A.; Obici, L.; Pazzola, G.; Croci, S.; Salvarani, C.
Abstract : Background: Cryopyrin-associated periodic syndromes (CAPS) are a group of rare autoinflammatory diseases caused by dominantly inherited mutations, or de novo gain-of function mutations within CIAS1/NLRP3 gene. Q703K is a variant of CIAS1/NLRP3 gene with unknown pathogenic significance, being also present with an allele frequency of 5% in Caucasian healthy population. It is still unclear whether Q703K has to be considered a low penetrance mutation or a functional polymorphism, whereas it is detected in patients with clinical manifestations suggestive for CAPS. Methods: We describe the cases of two siblings who presented with clinical manifestations suggestive for a periodic auto-inflammatory disorder and brilliantly responded to anti-IL1 treatment with anakinra. Molecular analysis of the CIAS1/NLRP3 gene in the two cases and in their first-degree relatives was performed, and a genotype/phenotype correlation of the carriers of Q703K allele was assessed. Detailed information regarding family history and the genealogical tree was also collected Results: A 30-year-old man and a 35-year-old woman siblings came to our attention complaining of periodic clinical manifestations lasting since their infancy and young adult age, respectively. The male patient had been experienced recurrent episodes of high-grade fever (T. max 41°C) associated with morning headache, urticarial rash, and conjunctivitis, lasting from 3-5 days through >7 days. The female patient had been suffered from asthenia and chronic musculoskeletal pain since the age of 21, first diagnosed as fibromyalgia. The symptoms were accompanied by episodic low-grade fever (T. max 37.5°, lasting few days); laboratory tests showed persistent increase of acute phase reactants (APR). Serum amyloid A (SAA) levels were found high in both patients (157 mg/L and 54.7 mg/L, respectively, n.v. <6.4). Anti-IL-1 treatment with anakinra quickly controlled the constitutional symptoms and allowed to achieve a significant decrease of the APR in both cases. The molecular analysis of the CIAS1/NLRP3 gene detected heterozygosity for Q703K variant in exon 3 in both patients. The assessment of the genealogical tree and their family history revealed episodes of conjunctivitis and arthralgia in their mother since her young adult age, without any correlation with cold exposure nor fever. The molecular analysis showed in her case homozygosity for Q703K variant. The family history also revealed that their maternal aunt had been suffered from urticarial rash episodes after cold exposure without fever, since the age of 52. Conclusions: The phenotypic expression observed in carriers of Q703K variant suggests that other genetic and environmental factors, currently unknown, might contribute to the atypical mild clinical autoinflammatory manifestations observed in such cases. However, the remarkable response to IL-1 blockade in our cases confirms the pivotal role of IL-1 in determining the clinical features. Further larger series are needed in order to investigate whether Q703K variant alone might be responsible for milder "CAPS-like" phenotype. Disclosure of Interest: None declared